Substantiation of the collocation method for one class of systems of integral equations - Khalilov, E. G. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We present the substantiation of the collocation method for a system surface integral equations of the boundary-valueproblem of conjugation for the Helmholtz equations. Moreover, we construct a sequence convergent to the exact solutionof the boundary-value problem of conjugation and estimate its error.